Characterization of the human protein S gene promoter: a possible role of transcription factors Sp1 and HNF3 in liver - Tatewaki, Hideki; Tsuda, Hiroko; Kanaji, Taisuke; Yokoyama, Kazunari; Hamasaki, Naotaka (Thrombosis and Haemostasis, 2003)
Protein S is a vitamin-K-dependent plasma glycoprotein that serves as a cofactor for activated protein C in the protein C anticoagulation pathway, which regulates blood coagulation by inactivating factors Va and VIIIa. Mechanisms regulating the expression of the protein S gene remain unknown to date. The aim of this study was to characterize the cis-acting DNA elements of the human protein S gene in liver.We found that liver cell lines (HepG2 and PLC) transcribed the human protein S gene to mRNA, whereas non-liver cell lines (HEK293 and HeLa cells) either transcribed the gene weakly or not at all. Isolation and analysis of tissue-specific gene expression in HepG2 and HeLa cells of the 5’-flanking region from-6183 to +294 of the protein S gene indicated that the consensus binding motifs to HNF3 and Sp1 or MAZ transcription factors in the flanking region are essential for protein S gene expression. Exogenous expression of the Sp1 gene augmented the protein S-reporter gene expression in HepG2 or PLC cells but had no effect in HeLa cells. Taken together, we would conclude that transcription factors of HNF3, MAZ, and Sp1 are required for high-level expression of the protein S gene in hepatic cells, but in non-hepatic cells such as HeLa cells, an unknown factor(s) binds to the Sp1 region and disturbs the action of Sp1 and MAZ.
Keywords: Gene expression; protein C/S pathway; transcription factors